The Influence of Principal Leadership and Teacher Work Culture on the Work Loyalty of Elementary School Teachers - Suarni, Suarni (Journal of Educational Sciences, 2022)
This study aims to determine the effect of principal's leadership on teacher work loyalty, the influence of teacher work culture on teacher work loyalty, and find out whether there is an effect of principal leadership and teacher work culture together on teacher work loyalty. The research method used a survey with a quantitative descriptive approach. The research population was included all of elementary school teachers in Cluster IV, Bukit Kapur sub-district, Dumai City was 117 teachers, with a total sample of 91 teachers. The sampling technique used Simple Random Sampling. Data collection techniques were carried out using a questionnaire. The results of the study indicated that there was a direct positive influence of principal's leadership on teacher work loyalty. There was a direct positive influence of teacher work culture on teacher work loyalty and there was an influence of principal's leadership and teacher work culture on teacher work loyalty together.